Comparative Phytochemical and Biological Study of Tinospora cordifolia (Thunb.) Miers and Justicia adhatoda L. Plants Collected from West Rukum of Nepal - Oli, Biraj; Ghimire, Gyanendra; Dhakal, Bijay; Amatya, Neetu; Adhikari, Deepjyoti; Bhandari, Netra Lal (Journal of Nepal Chemical Society, 2023)
Medicinal plants contained an impressive number of modern drugs and are believed to be a precious natural reservoir that has been continuously studied for its pharmacological activities against various ailments. Tinospora cordifolia and Justicia adhatoda are widely used shrubs in folk and ayurvedic systems of medicine. Phytochemical screening of different fractions of the extract of the bark of T. cordifolia and leaf, stem, and flowers of J. adhatoda was done and results show the presence of alkaloids, flavonoids, phenolics, glycosides, terpenoids in both plants. The antibacterial potency of medicinal plant extracts has been tested against Bacillus subtilis ATC6051 and Enterococcus faecalis ATCC29212 by disc diffusion assay. The leaves extract of J. adhatoda showed good antibacterial activities towards both the Enterococcus faecalis and Bacillus subtilis bacteria, however, the extract of T. cordifolia was found not soo effective with those bacteria. The methanol extract of T. cordifolia stem showed the strongest 2,2-diphenylpicrylhydrazyl (DPPH) radical scavenging activity with IC50 values 8.213μg/mL very close to standard ascorbic acid (22.451 μg/mL). Furthermore, results showed that T. cordifolia is a good source of antioxidants as compared to the J. adhatoda. The total phenolic content (TPC) was highest in methanolic extract of T. cordifolia (46.463 mg GAE/g extract) while the J. adhatoda had lower values (31.167 mg GAE/g extract) by taking gallic acid as a standard. The total flavonoid content (TFC) was highest in methanol extract of J. adhatoda leaves (13.030 mg QE/g extract) while T. cardifolia had lower values (2.112 mg QE/g extract) which were determined by taking quercetin as a standard. The result revealed that the TPC is higher in T. cordifolia and TFC value higher in J. adhatoda and that can be correlated with the antimicrobial and antioxidant properties of phytoconstituents although the plants have been used for the similar ethnomedical purpose in society.